2015
DOI: 10.1016/j.gep.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression pattern of Annexin A6 in chick neural crest and placode cells during cranial gangliogenesis

Abstract: The cranial trigeminal and epibranchial ganglia are components of the peripheral nervous system that possess an important somatosensory role. These ganglia arise from the intermixing and coalescence of two different migratory cell types, neural crest cells and neurogenic placodes cells, and thus typify the phenomena of cell migration and intercellular interactions for their creation. The underlying molecular mechanisms of ganglia formation, however, are still poorly understood. To address this, we have analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…2B, D′, arrowheads, n = 9 ganglia), further validating the specificities of the Annexin A6 MO and antibody. We also observe comparable results for epibranchial neurons depleted for Annexin A6 since they possess a similar pattern of Annexin A6 expression and subsequent neurogenesis (see (Shah and Taneyhill, 2015) (Smith et al, 2015); data not shown). Collectively, our results indicate that depletion of Annexin A6 from trigeminal or epibranchial neuronal precursors does not adversely affect trigeminal or epibranchial neuron ingression, differentiation, or position.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…2B, D′, arrowheads, n = 9 ganglia), further validating the specificities of the Annexin A6 MO and antibody. We also observe comparable results for epibranchial neurons depleted for Annexin A6 since they possess a similar pattern of Annexin A6 expression and subsequent neurogenesis (see (Shah and Taneyhill, 2015) (Smith et al, 2015); data not shown). Collectively, our results indicate that depletion of Annexin A6 from trigeminal or epibranchial neuronal precursors does not adversely affect trigeminal or epibranchial neuron ingression, differentiation, or position.…”
Section: Resultssupporting
confidence: 77%
“…Our previous studies demonstrated that Annexin A6 is expressed predominantly on the membrane of placodal sensory precursors in the ectoderm and their neuronal derivatives that have ingressed into the mesenchyme (Shah and Taneyhill, 2015). To determine the function of Annexin A6 within cranial sensory neurons, we used an ectodermal electroporation method described previously (Shiau et al, 2008) to introduce the control or Annexin A6 MO into the precursor sensory ectoderm at Hamburger-Hamilton (HH) 10.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations